Buwayhid Library and its Management: A Historical Analysis (Eastern Librarian, 2012)
Like the ancient Mesopotamian, Egyptian and Roman library, Muslim library has been introduced from the early age of Islam in demand of time. In the meantime, the emergence of Hazrat Muhammad (Sm.) had started a new era of knowledge and science in Islam. From the very beginning of Islamic civilization many institutions were established and renowned intellectuals and scholars of different fields were associated with those institutions. They made various worthy researches for the development of Muslim knowledge and sciences, in badly need of many libraries. So after several years when the Muslims came closer to the Persian literature and Greek sciences the Islamic library started its journey in the 7th century. So, for the acquisition of knowledge Muslim library has been initiated from the very beginning of Islamic heritage which was started with the mosque though formally introduced by the Baitul Hikmah, by Abbasid khalifa Al-Mamun (813-833). Gradually by the expansion of Islam it was circulated in various countries of the world. In these process Buwayhid ruler came closer to the Abbasid and taught the process of establishing various royal, private and public library. After the inception of royal library the Buwayhid introduced various important functions such as, collection of books, preservation system, translation, cataloguing, inclusion and clarification of the books. Besides these, recruitment, promotion, management of archives and modern system of budgeting were also salient features of their library management. The present study is an attempt to analyze the nature of the Buwayhid royal, private and public libraries. The study will also cover exclusively its library management and its various administrative functions. DOI: http://dx.doi.org/10.3329/el.v23i1.12120 Eastern Librarian Vol.23(1) 2012 pp.51-63